Genetic Study of Propoxur Resistance—A Carbamate Insecticide in the Malaria Mosquito, Anopheles stephensi Liston. (28th December 2010) - Sanil, D.; Shetty, N. J.
Abstract : Anopheles stephensi Liston (Diptera: Culicidae) is the urban vector of malaria in the Indian subcontinent and several countries of the Middle East. The genetics of propoxur resistance ( pr ) in An. stephensi larvae was studied to determine its mode of inheritance. A diagnostic dose of 0.01 mg/L as recommended by WHO was used to establish homozygous resistant and susceptible strains. Reciprocal crosses between the resistant and susceptible strains showed an F1 generation of incomplete dominance. The progenies of backcrosses to susceptible parents were in 1 : 1 ratio of the same phenotypes as the parents and hybrids involved. The dosage mortality (d-m) lines were constructed for each one of the crosses, and the degree of dominance was calculated. It is concluded that propoxur resistance in An. stephensi larvae is due to monofactorial inheritance with incomplete dominance and is autosomal in nature.